Home‐institutional Imprinting and Lobbying Expenditure of Foreign Firms: Moderating Effects of Experience and Technological Intensity. (10th November 2017) - Shirodkar, Vikrant; Konara, Palitha; McGuire, Steven
Abstract: The issue of whether a firm's 'home' environment influences its non‐market activities in a 'host' country is being increasingly discussed in the international business literature. In this paper, we use institutional and organizational imprinting theories to argue that multinational enterprises (MNEs) founded in countries with stronger regulatory institutions are likely to spend more on lobbying in a host country compared to MNEs founded in countries with weaker regulatory institutions. We also argue that this effect is moderated by the MNE's overall experience, its experience within the host country and its technological intensity. We test our hypotheses using a sample of 378 foreign MNEs (among the largest 500) operating in the USA, spanning the eight year period 2006−2013, and representing 29 home countries. Our results support our hypothesis on the relationship between home‐institutional imprinting and overseas lobbying expenditure, as described above. Our results also support our arguments that MNEs' overall experience and technological intensity reduce the imprinting effect of home institutions on lobbying expenditure; however, our moderating effect of host‐country experience on this relationship is not supported.